Pengaruh Bi Rate, Inflasi, Nilai Tukar, Ekspor, Jumlah Uang Beredar Terhadap Cadangan Devisa Di Indonesia - Saputra, Jacksen; Arsyadinata, Aldrin; Pratama, Mochammad Wahyu; Al Fauzhan, Shanityo Salman (Journal of Economics and Policy Studies (JEPS), 2025)
ABSTRACT This study examines the impact of the BI rate, inflation, exchange rate, exports, and money supply on Indonesia’s foreign exchange reserves from 2019 to 2024. Using a quantitative approach with multiple linear regression on monthly time-series data from Bank Indonesia, BPS, and the Ministry of Trade, the findings show that the BI rate has no significant effect, while inflation exerts a significant negative influence on foreign exchange reserves.. In contrast, the exchange rate, exports, and money supply show positive and significant effects on foreign exchange reserves, highlighting the crucial role of external sector performance and domestic liquidity in supporting reserve accumulation. Collectively, the five independent variables account for 88.5% of the variation in foreign exchange reserves, with the remaining 11.5% explained by factors beyond the model.. These findings emphasize the importance of coordinated macroeconomic policies to maintain inflation stability, strengthen the exchange rate, promote exports, and effectively manage liquidity in order to sustain Indonesia’s foreign exchange reserves and support overall macroeconomic stability. ABSTRAK Studi ini meneliti dampak BI Rate, nilai tukar, inflasi, ekspor, dan jumlah uang beredar terhadap cadangan devisa Indonesia pada periode 2019–2024 dengan menggunakan pendekatan kuantitatif melalui regresi linear berganda. Studi ini menggunakan data runtut waktu bulanan yang bersumber dari Kementerian Perdagangan, Bank Indonesia, Badan Pusat Statistik. Studi ini membuktikan bahwa BI Rate tidak berdampak signifikan terhadap cadangan devisa secara parsial, sementara inflasi berpengaruh negatif dan signifikan. Sebaliknya, nilai tukar, ekspor, dan jumlah uang beredar terbukti berdampak signifikan positif. Kelima variabel tersebut mampu menjelaskan 88,5% variasi cadangan devisa Secara simultan, sedangkan 11,5% dipengaruhi faktor dari luar model. Hasil studi ini menunjukkan pentingnya kebijakan makroekonomi yang terintegrasi untuk menjaga stabilitas cadangan devisa dan perekonomian nasional.